Using NCBI BLAST. Issue 14 (2nd May 2017) - Stover, Naomi A.; Cavalcanti, Andre R.O.
Abstract: BLAST is the most widely used software in bioinformatics research. Its main function is to compare a sequence of interest, the query sequence, to sequences in a large database. BLAST then reports the best matches, or "hits, " found in the database. This simple program has two primary applications. First, if the function of the query sequence is unknown, it may be possible to infer its function based on the recognized functions of similar sequences. Second, if the researcher has a query sequence with a known function, it may be possible to identify sequences in the database that have similar functions. The utility of BLAST therefore depends on the researcher's choice of query sequence and database. An appreciation for the functions and limitations of BLAST is vital to using this program effectively. This unit will introduce the basic concepts behind BLAST, walk through BLAST searching protocols, and interpret common results. © 2017 by John Wiley & Sons, Inc.